Implementasi Internet of Things pada Sistem Informasi Pelacakan Kendaraan Bermotor Menggunakan GPS Berbasis Web - I Wayan Agus Arimbawa; Abdul Chalel Rahman; Andy Hidayat Jatmika (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
The research of motor vehicle tracking system using GPS have been done by some researchers. However those researches still have problems, such as the location’s accuracy, data transmision that is still manual using SMS, and systems that have not been integrated with the web server. This research applies the concept of Internet of Things on a vehicle system device consisting of four parts. There are an Arduino Uno R3 microcontroller as part of control, GY-NEO6MV2 GPS module providing position information, SIM900A GSM/GPRS module used to send or receive data from server, and web-based information system used to monitor position of vehicle. From the results it can be concluded that GPS Tracker device that was designed has ran well and produced an average error difference of 2,457 meters.